The Reality of Art Worlds. The Tv Spectacle of the Artistic Field - Federico Boni (piano b, 2019)
Over the last few years, an increasing number of reality television shows are being produced and broadcast, centered on the art worlds. The first show of this kind was Artstar (Gallery HD, 2006), where eight artists (out of over 400 applicants) participated in a group exhibition at Deitch Projects art gallery. It only lasted one season, but it was soon followed by similar reality shows such as School of Saatchi (BBC, 2009), where young artists compete for a chance to be chosen by famous art collector Charles Saatchi to showcase their work in a worldwide renowned gallery; Work of Art: The Next Great Artist (Bravo, 2010), in which artists compete for a solo exhibition and a cash price of $ 100,000; Gallery Girls (Bravo, 2012); Street Art Throwdown (Oxygen, 2015); and Art Breaker$ (Ovation, 2015). In their variants, all these programs both depict and enact the commodification of the art worlds, where artistic celebrity is configured as an end-product that has commodity value. These talent shows essentially involve participants learning to labour for success in the art worlds, while at the same time co-creating the entertainment spectacle with little guaranteed return. Furthermore, this systematic production of artistic celebrity thrives on competing discourses that construe artistic talent as the product of both merit and manufacture, “authenticity” and (the) market.